Hw01 - badruddin (ssb776) HW01 Radin (57410) This print-out...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
badruddin (ssb776) – HW01 – Radin – (57410) 1 This print-out should have 20 questions. Multiple-choice questions may continue on the next column or page – fnd all choices beFore answering. HW01 is a review oF M408K material. It overlaps HW02 and HW03. 001 10.0 points Determine iF lim x →∞ b ln(7 + 2 x ) - ln(2 + 5 x ) B exists, and iF it does fnd its value. 1. limit does not exist 2. limit = ln 2 5 correct 3. limit = ln 2 7 4. limit = ln 7 2 5. limit = ln 5 2 Explanation: By properties oF logs, ln(7 + 2 x ) - ln(2 + 5 x ) = ln p 7 + 2 x 2 + 5 x P = ln p 7 /x + 2 2 /x + 5 P . But lim x →∞ 7 /x + 2 2 /x + 5 = 2 5 . Consequently, the limit exists and limit = ln 2 5 . 002 10.0 points Determine iF lim x →∞ sin 1 p 1 + 4 x 5 + 2 x 2 P exists, and iF it does, fnd its value. 1. limit = π 3 2. limit = π 4 3. limit = π 6 4. limit = π 2 5. limit = 0 correct 6. limit does not exist Explanation: Since lim x →∞ 1 + 4 x 5 + 2 x 2 = 0 , we see that lim x →∞ sin 1 p 1 + 4 x 5 + 2 x 2 P exists, and that the limit = sin 1 0 = 0 . 003 10.0 points Determine iF lim x →∞ tan 1 p 1 + 4 x 5 + 2 x 2 P exists, and iF it does, fnd its value. 1. limit = 0 correct 2. limit = π 4 3. limit = π 2 4. limit = π 3
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
badruddin (ssb776) – HW01 – Radin – (57410) 2 5. limit = π 6 6. limit does not exist Explanation: Since lim x →∞ 1 + 4 x 5 + 2 x 2 = 0 , we see that lim x →∞ tan 1 p 1 + 4 x 5 + 2 x 2 P exists, and that the limit = tan 1 0 = 0 . 004 10.0 points Express the function f ( x ) = sin 2 x + 5 cos 2 x in terms of cos 2 x . 1. f ( x ) = 2 - 3 cos2 x 2. f ( x ) = - 3 + 2 cos 2 x 3. f ( x ) = 3 - 2 cos2 x 4. f ( x ) = - 2 - 3 cos 2 x 5. f ( x ) = - 2 + 3 cos 2 x 6. f ( x ) = 3 + 2 cos2 x correct Explanation: Since sin 2 x = 1 2 (1 - cos 2 x ) , cos 2 x = 1 2 (1 + cos 2 x ) , we can rewrite f ( x ) as f ( x ) = 1 2 (1 - cos 2 x ) + 5 2 (1 + cos 2 x ) . Consequently,
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 09/23/2009 for the course M 57420 taught by Professor Radin during the Fall '09 term at University of Texas at Austin.

Page1 / 8

Hw01 - badruddin (ssb776) HW01 Radin (57410) This print-out...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online